Perspective Planning for Community forestry Plantation- a Case Study - Laxmi, Vijay; Pandey, V. K. (Indian Forester, 1994)
The paper shows an optimum tree combination plan for community wastelands to meet the fuel and fodder requirements of the local people with their participation in a long term perspective. The linear programming technique was used for the optimum tree mix plan for plantation in 800 hectares of community wastelands of 34 Villages. The feasible solution were obtained for the entire area in aggregate and for different altituds. In segregate altitude-wise plan. The linear regression analysis was used to see the factor which affects people's participation. It was found that size of land holdings, level of education, contact with extention workers and scientific orientation, people's over all modernity. Plantation of locally desired tree species and distance of present site of fodder and fuel collection had all positive and significant impact where as the founds of age of respondent, distance of site of plantation and masa media exposure were found to have negative but significant impact on people's participation in Community Forestry Programme.